Preventing money laundering: a test of situational crime prevention theory. Issue 4 (3rd October 2016) - Gilmour, Nicholas
Abstract : Purpose: This paper aims to discuss the findings of a UK-based research study that sought to explore the applicability of situational crime prevention towards money laundering undertaken through the purchasing of high-value portable commodities. Design/methodology/approach: This paper presents exploratory findings from research conducted between 2011 and 2013 in the UK. The research sought to identify the process, steps and vulnerabilities behind money laundering through the purchasing of high-value portable commodities and whether the introduction of situational crime prevention techniques could reduce vulnerabilities in the existing environment. Findings: Despite significant research into money laundering typologies, the use of high-value portable commodities has remained largely untouched, regardless of the increased implementation of anti-money laundering policies and procedures. This paper demonstrates how the purchasing of high-value portable commodities is extremely vulnerable to money laundering – while identifying how the successful application of situational crime prevention is possible – but inherently it depends on various characteristics directly and indirectly facilitating each stage of the money laundering process. Research limitations/implications: This paper is of value to government policymakers, regulators and financial institutions considering future preventative measures. It is also of value to financial investigators and law enforcement agencies intent on investigating money laundering. While the paper relies on data from the UK, the overall findings are such that wherever cash-intensive businesses exist, so too does the opportunity for money laundering through the financial arrangement retained by such businesses. Originality/value: This paper presents new research on the direct link existing between high-value portable commodities and money laundering in the UK and the viability of techniques for situational crime prevention despite significant research having previously taken place to identify and develop money laundering typologies.